ANALISIS KEIKUTSERTAAN INDONESIA DALAM LIBERALISASI MULTILATERAL TERHADAP KINERJA SEKTOR BERAS DAN GULA DALAM MEWUJUDKAN KETAHANAN PANGAN - Adrian D Lubis; Reni K Arianti (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2012)
Lots of people believe that multilateral liberalization will reduce Indonesia capability to maintain national food security, especially for rice and sugar. However, this study that use multiregression analysis with dummy variabel and GTAP found that import of rice and sugar increase due to lack of capability to fulfill national consumption. Therefore, Indonesia must increase its rice and sugar productivity to fulfill national food security in liberalization regime.Keywords : Trade Liberalization, Food Security, Multiregression, GTAP Model